Effect of Crack Patterns in Calcified Plaque on Lumen Area after Stenting for a Severe Calcified Coronary Artery (from the Optical Frequency Domain Imaging-Guided Percutaneous Coronary Artery Intervention for Calcified Lesion Registry) - Hirooki Higami; Hiroaki Matsuda; Hikaru Tateyama; Yoriyasu Suzuki; Kazuaki Kaitani (Journal of Interventional Cardiology)
Background. Severely calcified coronary artery stenting remains a challenge due to stent thrombosis, target vessel failure, and higher mortality. Moreover, optimal vessel preparation for calcified plaque with a crack formation pattern has not been established yet. We aimed to identify the effect of crack formation in calcified plaque in the coronary artery on the lumen area after stenting. Materials and Methods. We evaluated 50 consecutive patients undergoing drug-eluting stent implantation for severely calcified lesions by using optical frequency domain imaging (OFDI) (54 lesions); we analyzed OFDI image slices every 3 mm and evaluated the segments of 242 images in those who had the arc of calcium more than 180°. Crack formation in calcified plaque was classified into three types: type 0, no cracks; type 1, no dissection between calcified plaque and vessel wall; and type 2, any dissection between calcified plaque and vessel wall. Results. Type 2 had a significantly higher area expansion ratio between preballooning and poststenting (type 0, 196% (interquartile range (IQR), 163–244); type 1, 210% (IQR, 174–244); type 2, 237% (IQR, 203–294)). Conclusions. The dissection between calcified plaque and vessel wall was a significant factor affecting lumen area expansion after stenting.